Base pair editing in goat: nonsense codon introgression into FGF5 results in longer hair. (23rd July 2019) - Li, Guanwei; Zhou, Shiwei; Li, Chao; Cai, Bei; Yu, Honghao; Ma, Baohua; Huang, Yu; Ding, Yige; Liu, Yao; Ding, Qiang; He, Chong; Zhou, Jiankui; et al.
Abstract : The ability to alter single bases without homology directed repair (HDR) of double‐strand breaks provides a potential solution for editing livestock genomes for economic traits, which are often multigenic. Progress toward multiplex editing in large animals has been hampered by the costly inefficiencies of HDR via microinjection of in vitro manipulated embryos. Here, we designed sgRNAs to induce nonsense codons (C‐to‐T transitions) at four target sites in caprine FGF5, which is a crucial regulator of hair length in mammals. Initial transfections of the third generation Base Editor (BE3) plasmid and four different sgRNAs into caprine fibroblasts were ineffective in altering FGF5 . In contrast, all five progenies produced from microinjected single‐cell embryos had alleles with a targeted nonsense mutation. The effectiveness of BE3 to make single base changes varied considerably based on sgRNA design. In addition, the rate of mosaicism differed between animals, target sites, and tissue type. The phenotypic effects on hair fiber were characterized by hematoxylin and eosin, immunofluorescence staining, and western blotting. Differences in morphology were detectable, even though mosaicism was probably affecting the levels of FGF5 expression. PCR amplicon and whole‐genome resequencing analyses for off‐target changes caused by BE3 were low at a genome‐wide scale. This study provided the first evidence of base editing in large mammals produced from microinjected single‐cell embryos. Our results support further optimization of BEs for introgressing complex human disease alleles into large animal models, to evaluate potential genetic improvement of complex health and production traits in a single generation. Abstract : Taking advantage of the base editing (BE3) system, we successfully achieved modest efficiencies of single base substitutions at multiple target sites of the FGF5 gene in goats. We provide multiple lines of evidence to detail the genotypic and phenotypic changes induced by BE3. We conduct whole genome resequencing of five mutant animals and four controls to demonstrate that the BE3 induced off‐target mutations are rare and largely depend on sgRNA design.